The Relationship Between Perception of Organizational Structure and Human Resource Development - Maleki, Ahmad; Karimi, Fariba (International Journal of Asian Social Science, 2014)
This study explores the relationship between Perception of organizational structure and human resources development for the employees of Mobarakeh Esfahan Steel Company .For this study a descriptive method of a correlational nature was employed. The statistical population comprised all the Mobarakeh Esfahan Steel Company employees, from whom, using a systematic sampling technique and Cochran’s Sample Size Estimation Formula, 375 employees were selected for the sample size. The data collection tool comprised two self-made questionnaires on the organizational structure with the aspect of formality, centralization and complexity and the other questionnaire for the human resources development inventory with the aspect of perceptional skills is self-confidence, occupational conscience, self-evaluation, occupational skills, creativity, shift-adaption and voluntary team work. Using Cronbach’s alpha coefficient, the reliability coefficient for the organizational structure questionnaire was 0/79 and for the human resources development questionnaire was 0/90. There is an inverse relation between all three dimensions of formality, centralization and complexity with a number of Human Resources Development constructs i.e. occupational conscience, self-evaluation and occupational skills. There was a negative relation between formality, creativity and voluntary team work, centralization, self-confidence and creativity and complexity with perceptional skills, self-confidence and voluntary team work with Human Recourses Development. Step wise Regression findings showed that the best human resources development predictors among Mobarakeh Esfahan Steel Complex employees were complexity in the first stage and centralization combined with complexity in the second stage.